Fate of Escherichia coli O157:H7 and Salmonella enterica in the manure-amended soil-plant ecosystem of fresh vegetable crops: A review. (August 2015) - Ongeng, Duncan; Geeraerd, Annemie Hellena; Springael, Dirk; Ryckeboer, Jaak; Muyanja, Charles; Mauriello, Gianluigi
Abstract Enterohemorrhagic Escherichia coli (EHEC) and Salmonella enterica have been implicated in several disease outbreaks linked to consumption of fresh vegetables. Both ruminant and non-ruminant animals carry EHEC and S. enterica in their gastrointestinal tracts and can shed the pathogens in the faecal matter both in symptomatic and asymptomatic states. Application of animal waste in soil fertility management and irrigation of crops with contaminated waste water has been recognised as an important route through which EHEC and S. enterica can contaminate fresh vegetables during primary production. The behavior of E. coli O157:H7 and S. enterica in the agricultural environment has been extensively studied in the last decades. Several microbiological detection methods have been applied. This review therefore puts together current knowledge on the behavior of E. coli O157:H7 and S. enterica in the manure-amended soil-plant ecosystem of fresh vegetable crops during cultivation under various environmental conditions. The review focuses on methodological issues involved in undertaking survival studies and makes comparative analysis of experimental results obtained from studies conducted under controlled environmental conditions integrating results obtained from field experiments. Finally, a theoretical discussion on the potential likely impact of climate change on pre-harvest safety of field-cultivated vegetables is highlighted.